Sindhi Cuisine: A Study Of Evolution And Eating Habits (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: Cuisine introduces a pleasant, explanatory, and incredible story of the interaction  among history, culture and food. It includes all the elements of time: past, present, and future.  Throughout history, food has played a critical and defining part in individual’s culture and  overall development of diaspora. Objective: To study common Sindhi food items consumed  and to identify the food habits of Sindhi’s. Methodology: The data was collected from 100  Sindhi’s from Bhopal city. Results: Various Sindhi Cuisine items were identified during the  study which gave a new insight of common food items. Food habits of Sindhi community  was also found to be very well distributed throughout the day covering all food groups.  Conclusion: Sindhi’s has a unique culture and food habits, the use of ingredients and cooking  style adopted from their Pakistani culture which still prevails due to the cultural values. There  is also other culture influence on their food. There is a need to preserve their authentic recipes  and a has a big scope for study.
Keywords: Cuisine; Diaspora; Eating habits; Evolution; Culture